COMPARATIVE PERSPECTIVES BETWEEN WESTERN AND ISLAMIC SCHOLARS TOWARDS THE CONCEPT OF CIVIL SOCIETY - Jamal Mohammed Ameen Hussein (Journal of Islamic, Social, Economics and Development, 2023)
There has long been a tradition of volunteer organisations in civil society serving the general welfare. They function as a bridge between the populace and the government, relaying the needs and wants of the populace via pressure and protests to the government in order to secure justice, enhance democracy, and promote free speech. In this respect, there are differences in viewpoints between Western and Islamic philosophers due to the historical context of the activities of civil society organisations (CSOs). Due to its acceptance and rejection of CSOs; operations in the manner in which they are promoted, it has grown significantly in prominence and sparked debate among Islamic scholars. The diverse perspectives held by Western and Islamic philosophers are analysed in this study using historical analysis and descriptive methodologies. Although the notion of civil society is developed in Western thought, some Islamic scholars think it is tied to Islam and vital to the general welfare. Others, on the other hand, think that civil society and Islam cannot coexist.